Trends in structural engineering - Krishna, Prem; Iyer, Nagesh R. (Journal of Structural Engineering, 2024)
Structural engineering has been the backbone of human development from the ancient times, and this field continually adapts and evolves by embracing innovative approaches and emerging trends to meet the ever-changing demands. In this paper, a bird’s eye view on the trends that will shape the structural engineering in near future is provided. Some of the emerging technologies such as building information modeling, artificial intelligence, machine learning, robotics, automation, that have the potential to improve productivity, safety, sustainability and resilience of the built environment are discussed. It is noted that the present day challenges require a different approach to education and innovation in civil engineering, along with leveraging technology transfer and interdisciplinary collaboration.